2012
DOI: 10.1111/j.1752-0606.2011.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutting to Live: A Phenomenology of Self‐Harm

Abstract: This exploratory study utilizes a phenomenological methodology as described by Moustakas (Phenomenological research methods, Sage Publications, 1994). Data were gathered via qualitative face‐to‐face interviews from a midsize southwestern community. Eleven participants, ten females and one male, were included in this study. Data suggested three categories that described the participants’ experiences of self‐harm: Self‐harm is Misunderstood, Self‐Harm has a Role, and Advice to Professionals. Among these categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 33 publications
6
58
0
7
Order By: Relevance
“…In cyberspace groups, positive social identities appeared to be constructed through reciprocity when members gave and received support (Brown & Kimball 2013;Haberstroh & Moyer 2012). This was assisted by not linking self-harm to suicide, and by exploring the person, not only their self-harm.…”
Section: Identitymentioning
confidence: 99%
“…In cyberspace groups, positive social identities appeared to be constructed through reciprocity when members gave and received support (Brown & Kimball 2013;Haberstroh & Moyer 2012). This was assisted by not linking self-harm to suicide, and by exploring the person, not only their self-harm.…”
Section: Identitymentioning
confidence: 99%
“…For Mikolajczak, Petrides, and Hurry () self‐harm primarily constitutes an emotion regulation strategy to express distressing emotions, reduce dissociative symptoms, test interpersonal boundaries, and prevent aggression toward others. Other authors identify a lack of investigation into the motivations and functionality of self‐harm (the ‘whys’) resulting in a failure to understand treatment needs (Brown & Kimball, ; Laye‐Gindhu & Schonert‐Reichl, ; McAllister, ; Ougrin, ).…”
Section: Literature On Adolescent Self‐cuttingmentioning
confidence: 99%
“…() found that decreased family support predicted maintenance of self‐injury over a 12‐month interval, while increased family support predicted cessation. Additionally, adolescents who engage in self‐injury typically report the family environment to be critical, emotionally stifling, alienating, and lacking support and care (Baetens et al., ; Brown & Kimball, ; Bureau et al., ; Cox et al., ; Taliaferro, Muehlenkamp, Borowsky, McMorris, & Kugler, ). While prior findings consistently demonstrate a relationship between adolescent‐reported family functioning and self‐injury, family functioning is a dynamic, multidimensional account of a family life (e.g., Di Pierro et al., ; Epstein, Baldwin, & Bishop, ), and assessing family functioning from only one perspective restricts what can be inferred and generalized.…”
Section: Family Functioning and Self‐injurymentioning
confidence: 99%